Diet acids and alkalis influence calcium retention in bone - BUCLIN, T; COSMA, M; APPENZELLER, M; JACQUET, A.-F; DECOSTERD, L. A; BIOLLAZ, J; BURCKHARDT, P (Osteoporosis international, 2001)
The urine-acidifying properties of food constituents depend on their content of non-oxidizable acids or precursors. Acidifying constituents such as animal proteins may negatively affect calcium metabolism and accelerate bone resorption, thus representing an aggravating factor for osteoporosis. This four-period, double-crossover study investigated whether a diet intervention specifically focused on acid load could modify calcium metabolism in humans. Eight healthy volunteers underwent a four-day metabolic preparation with two types of diets, one rich in acid ash-forming nutrients, and one providing base-forming nutrients (including bicarbonate-rich mineral water), both having similar contents of calcium, phosphate, sodium, proteins and calories. On the fourth day, a single oral dose of 1 g calcium was given, either as carbonate or as gluconolactate. Serial blood and urine samples revealed that the diet affected blood pH (average difference 0.014, p=0.002) and urine pH (average difference 1.02, p<0.0001) in the expected direction, but had no influence on the absorption of the calcium supplement. The acid-forming diet increased urinary calcium excretion by 74% when compared with the base-forming diet (p<0.0001), both at baseline and after the oral calcium load, and C-telopeptide excretion by 19% (p=0.01), suggesting a skeletal origin for the excess calcium output. This observation confirms that renally excreted acids derived from food influence calcium metabolism, and that alkalizing nutrients inhibit bone resorption. Further studies are needed to determine the clinical impact of dietary counseling for avoiding diet acids as a preventive measure against osteoporosis.